(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the current status of hypertension among the elderly in Can Gio District, Ho Chi Minh City. Methods: A cross-sectional study was conducted on 321 elderly people in Can Gio District, Ho Chi Minh City, in January 2024. The information collected includes anthropometric measurements, blood pressure, smoking habits, and physical activity. Results: The prevalence of hypertension among the elderly was 74.8%, with Stage I, Stage II, and Stage III hypertension rates being 53.3%, 29.2%, and 17.5%, respectively. The prevalence of hypertension was similar between men and women (71.7% and 76%) and increased with age. The risk of hypertension in the group that adhered to physical activity recommendations was 20% lower compared to the group that did not engage in physical activity (PR=0.8; 95%CI: 0.7–0.9). Additionally, the elderly who smoked had a 1.3 times higher risk of developing HTN compared to those who did not smoke (PR=1.3; 95%CI: 1.2–1.5). Conclusions: The elderly have a high prevalence of hypertension, which is associated with age, physical activity, and smoking habits. It is necessary to raise awareness about hypertension, control risk factors, and promote physical activity.